Interdisciplinary Perspectives on Opioid Toxicity: Nursing, Medical, and Health Security Dimensions - Almutairi, Faten Aden; Almutairi, Mona Saleh; Almutairi, Nouf Saleh; Masrahi, Ahlam Ahmed Abdu; Tohary, Zahra Ibrahim Bohis; Somali, Ameerah Ali Ibrahim; Daghriri, Asrar Hassan Yahya; Daghriry, Shaima Ahmed; Alsafwani, Eman Ali Jassim; hadadi, Aisha abdow; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Opioid toxicity represents a critical public health crisis, characterized by a sharp rise in misuse, addiction, and fatal overdoses. This complex issue stems from the pharmacological effects of opioids on the central nervous system, particularly respiratory depression, and is fueled by a combination of prescribing practices, patient vulnerabilities, and social determinants. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to synthesize interdisciplinary perspectives on opioid toxicity, focusing on the integrated roles of nursing, medical management, and health security in prevention, acute intervention, and long-term harm reduction. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The analysis is based on a comprehensive review of clinical practices, including patient assessment, diagnostic criteria, and treatment protocols. It evaluates medical management strategies like Medication-Assisted Treatment (MAT) and nursing interventions for acute toxicity and monitoring. Health security dimensions, such as prescription drug monitoring programs and secure storage, are also examined. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective management requires a coordinated, multi-pronged approach. Key findings highlight the efficacy of naloxone for overdose reversal, the central role of MAT (e.g., buprenorphine, methadone) in treating Opioid Use Disorder (OUD), and the critical importance of nursing in continuous monitoring, patient education, and risk assessment. Health security measures are essential for preventing diversion. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Combating the opioid epidemic necessitates a unified strategy that bridges clinical care and public health. Interprofessional collaboration among nurses, physicians, pharmacists, and health security professionals is paramount to ensuring safe prescribing, effective overdose response, and sustainable recovery, thereby reducing morbidity and mortality.